Serum-Free Medium Provides a Clinically Relevant Method to Increase Olfactory Ensheathing Cell Numbers in Olfactory Mucosa Cell Culture - Daisuke Ito (Cell Transplantation, 2007)
There is much evidence to suggest that transplanted olfactory ensheathing cells may ameliorate the functional deficits associated with injuries to the nervous system, especially the spinal cord. For clinical implementation of this strategy it will be necessary to derive large numbers of these cells from an accessible and, preferably, autologous source, implying that olfactory mucosa would be ideal. Although olfactory ensheathing cells can be derived from olfactory mucosa, in routine culture conditions the proportion of these cells is unacceptably low for clinical purposes. This study compared the effect of culturing dissociated olfactory bulb and olfactory mucosa in two different media: one containing serum and one serum free. The results indicate that olfactory ensheathing cell proportion, and absolute cell numbers, is greatly increased in serum-free conditions. Further analysis suggests that serum-free medium has a differential effect on contaminating fibronectin-positive and p75-positive cells from olfactory bulb and olfactory mucosa. This study demonstrates that serum-free culture conditions provide a simple and useful means of deriving a sufficient number of olfactory ensheathing cells for transplantation and reveals a difference in biological behavior of the cells contained within olfactory bulb and olfactory mucosa.